THE ANALYSIS OF PERFORMANCE, INFORMATION, ECONOMY, CONTROL, EFFICIENCY, AND SERVICE (PIECES) IN-LIBRARY MANAGEMENT INFORMATION SYSTEMS POSTGRADUATE UIN ALAUDDIN MAKASSAR - Sitti Suhaerah; Saleh, Noerjihad; Ibrahim, Andi; La Ode Ismail Ahmad; Iskandar (Program Pascasarjana, UIN Alauddin Makassar, 2022)
This article elaborates the PIECES analysis of the management information system evaluated in terms of performance, information, control, efficiency, and services resulting from the applied library management information system. The type of research used is descriptive research with a qualitative approach. This research is a phenomenological approach where the purpose of this approach is to study in-depth the state of the postgraduate library at UIN Alauddin Makassar. The results of this research show the description of the library management information system applied by the postgraduate library of UIN Alauddin Makassar, where the software used has been integrated into the core activities of the library, namely the management of library materials, circulation services, search engine services, membership services, and reporting on library activities. The use of Slims 7 Candana software has met the needs of library management. However, the control section for reporting the number of visitors Postgraduate Library of UIN Alauddin Makassar does not apply visitor attendance at the library either manually or automatically by the management information system (visitor counter service). This section has no data input process, so the output process for reporting visitors neither exists.